2020
DOI: 10.3389/fpsyg.2020.01728
|View full text |Cite|
|
Sign up to set email alerts
|

The Influence of Unconscious Perceptual Processing on Decision-Making: A New Perspective From Cognitive Neuroscience Applied to Generation Z

Abstract: Cognitive neuroscience and its applied developments have revolutionized marketing. With advances in neuroscientific techniques, marketing has needed to refocus toward understanding issues like the area of the brain that should be stimulated to transform the consumer's intention to purchase into a real decision, how information is processed when making a decision, and how personality traits affect the purchase decision. Neuroscience has opened the door to the consumer's brain. For many years, scientists have in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
2
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 71 publications
1
2
0
Order By: Relevance
“…Comparing the results with other experiments that have used neuromarketing techniques [51,52] and recall tests [46,70], this research confirms that the most consistent messages from an emotional point of view are also the most remembered and those that can provoke, in that sense, changes in the subject's attitude.…”
Section: Discussionsupporting
confidence: 79%
See 1 more Smart Citation
“…Comparing the results with other experiments that have used neuromarketing techniques [51,52] and recall tests [46,70], this research confirms that the most consistent messages from an emotional point of view are also the most remembered and those that can provoke, in that sense, changes in the subject's attitude.…”
Section: Discussionsupporting
confidence: 79%
“…To date, AFFDEX has not been used frequently in the field of marketing, but several pioneering investigations have been carried out that have demonstrated its potential [51,52]. Similarly, in the field of health, it has been used in geriatrics [53], in forensics [54,55] and in pain studies [56].…”
Section: Methodsmentioning
confidence: 99%
“…44 Most authors agree that the centennial generation is composed of those born in the mid- or late-90s. 3,28,4449 Although it is difficult to trace the thin line that separates one generation from another (for example, millennials and Gen Z), 44 these studies have revealed a series of identity characteristics of Gen Z: (a) they attach great importance to the information shared on social networks 28 ; (b) they devote time and effort to the online shopping process 46 ; (c) they justify their purchases as intelligent, based on the opinions of their peers in networks, and they consider interpersonal communication about the product to be very relevant 49 ; (d) they have a strong desire for social interaction, participation, and co-creation of consumer experiences 45 ; (e) they use communication technologies to search for product information, and they are continuously on social networks 47 ; (f) they are oriented toward fashion and product customization 3 ; and (g) they are less loyal as customers than representatives of previous generations. 47…”
Section: Introductionmentioning
confidence: 99%